ANALYSIS OF STUDENTS' ERRORS IN WRITING DESCRIPTIVE TEXT AT SMKS PULAU BERAYAN DARAT MEDAN - Sinaga, Jenni Septiani; Tarigan, Natalia Widya Pasca; Simanulang, Monika Sari (English Language Teaching Prima Journal (ELT), 2023)
This research was conducted to describe students' errors in writing descriptive text. The purpose of this study is to analyze the errors made by students when writing descriptive text. This research method used descriptive qualitative method. This research was conducted at SMKS Pulau Berayan Darat Medan. There were 23 students in class XII, this study used a writing test instrument. Based on the research results, it was found that students made types of errors including omision as much as 27.5%, misinformation as much as 16.5%, addition as much as 9% and the most dominant error made was misordering as much as 47%. The occurrence of errors made by students can be caused by various factors, including lack of attention, inaccuracy, lack of grammar knowledge, or time pressure.